TROLLing: Scope and operation of an open respository for linguistic data - Andreassen, Helene N.; Conzett, Philipp; Høydalsvik, Stein; Janda, Laura Alexis; Longva, Leif; Nesset, Tore; Odu, Obiajulu (UiT The Arctic University of Norway, 2017)
Poster presentation for the 91st Annual Meeting of the Linguistic Society of America, January 5-8 2017, Austin TX. TROLLing ( https://opendata.uit.no/dataverse/trolling ) is an international archive for open linguistic data and statistical code (e.g. R scripts), launched in 2014 at UiT The Arctic University of Norway. With the increasing demand for archiving and sharing research data, as well as the problem of improper attribution, TROLLing aims to meet researchers’ needs by proposing safe storage of data files, and metadata templates based on international standards. Retrieval, sharing, and reuse of data is further facilitated by TROLLing being part of a global open data network. As regards attribution, the system automatically provides a dataset citation, comprising among other things the author name(s) and a persistent identifier (doi). A version control allows researchers to update their datasets at any time, previously published versions still being available open access. TROLLing is available to all subfields of linguistics, but is limited to structural data. The metadata template, however, allows linking to primary data, stored elsewhere.